Hubungan Antara Manajemen Waktu Dengan Prokrastinasi Akademik Pada Mahasiswa Yang Sedang Menyusun Skripsi - Mic Finanto Ario Bangun; Daya Sovranita (Jurnal Ilmiah Wahana Pendidikan, 2022)
Students who have taken thesis courses for more than one semester, there are obstacles the obstacles experienced while compiling thesis, these obstacles that make students procrastinate academically, what if students do not manage their time well, they will often experience academic procrastination. Academic procrastination is the behavior of avoiding academic assignments, procrastinating academic assignments in a way that causes failure, academic unhappiness and stress. Time management is the behavior of managing time as effectively as possible by using planning, scheduling, controlling time, making the most urgent priorities and organizing what is done, such as setting up a place to study and not delaying assignments. The purpose of this study was to determine the correlation between time management and academic procrastination in students who are preparing their thesis at Bhayangkara University, Jakarta Raya. Respondents taken amounted to 114 students, sampling using purposive sampling technique. The data collection method uses a time management scale and an academic procrastination scale. The results show that there is a significant negative relationship between time management and academic procrastination, namely (r) = -0.781 with a significance of 0.000 (p <0.05). Then the hypothesis proposed by the researcher is accepted, namely the higher the time management, the lower the academic procrastination and vice versa.